2017
DOI: 10.1016/j.jmbbm.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence elastography assessment of corneal viscoelasticity with a modified Rayleigh-Lamb wave model

Abstract: The biomechanical properties of the cornea play a critical role in forming vision. Diseases such as keratoconus can structurally degenerate the cornea causing a pathological loss in visual acuity. UV-A/riboflavin corneal collagen crosslinking (CXL) is a clinically available treatment to stiffen the cornea and restore its healthy shape and function. However, current CXL techniques do not account for pre-existing biomechanical properties of the cornea nor the effects of the CXL treatment itself. In addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 83 publications
(129 reference statements)
5
83
0
Order By: Relevance
“…Point dynamic loading is attractive as a source of shear waves, and an attractive noncontact localized method is the micro-air puff developed and applied extensively by the Larin group [45, 57, 63, 81, [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116], mainly to the cornea, but also to skin [108,116], cardiac and skeletal muscles [104], cartilage [101,106], fat and soft tissue tumors [97], and kidneys [112]. Similar to ARF-based excitation, an air puff can deliver a localized and well-controlled impulse stimulus, which can be accompanied by measurement of the tissue displacement or measurement of the air puff-induced elastic wave.…”
Section: Loading Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Point dynamic loading is attractive as a source of shear waves, and an attractive noncontact localized method is the micro-air puff developed and applied extensively by the Larin group [45, 57, 63, 81, [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116], mainly to the cornea, but also to skin [108,116], cardiac and skeletal muscles [104], cartilage [101,106], fat and soft tissue tumors [97], and kidneys [112]. Similar to ARF-based excitation, an air puff can deliver a localized and well-controlled impulse stimulus, which can be accompanied by measurement of the tissue displacement or measurement of the air puff-induced elastic wave.…”
Section: Loading Methodsmentioning
confidence: 99%
“…As well as recognizing that viscosity is not accounted for in the simple approach [181], boundary conditions must be carefully considered in the conversion of elastic wave speed into quantitative values of tissue viscoelasticity. For example, finite-element modelling (FEM) supported by experimental data showed that taking account of the stress at the tissue surface, e.g., imparted by a fluid, significantly reduced the group velocity of the elastic wave and, thus, could produce errors in quantification of elastic properties [109,111]. Geometrical factors, such as tissue curvature and thickness, also have profound effects on the measured elastic wave speed [105].…”
Section: Surface Elastic Wave Methods and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations